Implant density is not related to patient-reported outcome in the surgical treatment of patients with idiopathic scoliosis. (August 2018) - Charalampidis, A.; Möller, A.; Wretling, M-L.; Brismar, T.; Gerdhem, P.
Abstract : Aims: There is little information about the optimum number of implants to be used in the surgical treatment of idiopathic scoliosis. Retrospective analysis of prospectively collected data from the Swedish spine register was undertaken to discover whether more implants per operated vertebra (implant density) leads to a better outcome in the treatment of idiopathic scoliosis. The hypothesis was that implant density is not associated with patient-reported outcomes, the correction of the curve or the rate of reoperation. Patients and Methods: A total of 328 patients with idiopathic scoliosis, aged between ten and 20 years at the time of surgery, were identified in the Swedish spine register (Swespine) and had patient reported outcomes including the Scoliosis Research Society 22r instrument (SRS-22r) score, EuroQol 5 dimensions quality of life, 3 level (EQ-5D-3L) score and a Viual Analogue Score (VAS) for back pain, at a mean follow-up of 3.1 years and reoperation data at a mean follow-up of 5.5 years. Implant data and the correction of the curve were assessed from radiographs, preoperatively and a mean of 1.9 years postoperatively. The patients were divided into tertiles based on implant density. Data were analyzed with analysis of variance, logistic regression or log-rank test. Some analyses were adjusted for gender, age at the time of surgery, the flexibility of the major curve and follow-up. Results: The mean number of implants per operated vertebra in the low, medium and high-density groups were 1.36 (1.00 to 1.54), 1.65 (1.55 to 1.75) and 1.91 (1.77 to 2.00), respectively. There were no statistically significant differences in the correction of the curve, the SRS-22r total score, EQ-5D-3L index or number of reoperations between the groups (all p > 0.34). In the SRS-22r domains, self-image was marginally higher in the medium implant density group (p = 0.029) and satisfaction marginally higher in the high implant density group (p = 0.034). Conclusion: These findings suggest that there is no clear advantage in using a high number of implants per operated vertebra in the surgical treatment of patients with idiopathic scoliosis. Cite this article: Bone Joint J 2018;100-B:1080–6.